Identification of Malassezia species isolated from healthy skin in residents of Lima, Peru - Bejar, Vilma (2014)
Objective: To identify Malassezia species in healthy skin seborrhea areas in Lima inhabitants. Design: Cross-sectional study. Setting: Daniel Alcides Carrion Tropical Medicine Institute, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Asymptomatic persons. Interventions: Skin samples were collected from 129 asymptomatic residents of several districts of Lima city using Mariat and Adan-Campos’ technique. Malassezia isolation was performed in modified Dixon medium and incubated at 32° C for 7 days. Colonies were identified by macro and micro morphological characteristics and typing was determined by biochemical and physiological properties using Guillot’s technique. Main outcome measures: Malassezia species, participants’ gender, age and anatomical region. Results: Malassezia spp was isolated in 43.4% of the residents, 49.2% in men and 37.5% in women. From various body regions 68 cultures were positive: scalp 31 (45.6%), back 36 (52.9%) and frontal region 1 (1.5%). Isolates most common age group (47.2%) was that of adolescents-young (14-25 year-old). M. slooffiae was found in 83.8% and M. obtusa in 16.2% of cases. Conclusions: Malassezia spp. was present in healthy human skin. M. slooffiae was the predominant species in positive cases (83.8%) followed by M. obtusa (16.2%).